Physiology of Geographic Environment and Urban Relations: Example of 19th Century City Kilis - Akdemir, Ilhan Oguz; Incili, Omer Faruk (Marmara Univ, 2014)
Reflecting periods of pre- and post-industrial society in cities can easily be understood in two different urban physiology. City plan, street-street system, urban form is quite different from the industrial revolution offers a relief. City of Kilis, place of incorporation, registration processes, urban land use, historical period, traces of ethnic and cultural differences can easily be observed in the structure of the city. The advantages of the process of formation as a result of the geographical location of the city of Kilis 19th Century has become the urban center. In the next phase the 19th century urban fabric, shaped by the inhabitants of this city with the experience of settlement and urban architecture has been designed in a different city attractions. Urban land use has become a functional interaction of the natural and human environment. In this study the 19th century, the city street and road systems in order to specify system, public spaces, urban structure and format by examining the reflections of the social and economic life were analysed. In this way, the pre-industrial urban space in shaping the character of shareholders is highlighted items.
Keywords: Geography; Historical Geography; Kilis; Gaziantep; Kent Urban Land Use; 19th Century